Doctors' service orientation in public, private, and foreign hospitals - Andaleeb, Syed Saad; Siddiqui, Nazlee; Khandakar, Shahjahan (© 2007 Emerald Group Publishing Limited., 2016)
This article was published in the International Journal of Health Care Quality Assurance [© 2007 Emerald Group Publishing Limited. ] and the definite version is available at : http://doi.org/10.1108/09526860710743381 The Journal's website is at: http://www.emeraldinsight.com/doi/abs/10.1108/09526860710743381